PERTANGGUNG JAWABAN HUKUM PLATFORM MEDIA SOSIAL TERHADAP PUBLIKASI KONTEN YANG MENGANDUNG UNSUR PORNOGRAFI - Aziz, Fahrul Abdul; Anggraeni, Yulia (UNES Law Review, 2023)
The rapid flow of globalization affects the way of thinking and human lifestyle towards a more modern, rapid development of information technology and the high use of social media causes the world relationship to be borderless so as to increase the spread of various pornographic content resulting in cyber bullying, nonconsensual pornography, and trolling The negative impact is also experienced by adolescents and children who experience internet harassment. Therefore, technology companies as platform providers have the authority to identify publishable content. Several laws, especially Law No. 19 of 2016, have provisions regarding the protection of private life, however, until now there has been no regulation that clearly regulates the responsibility of technology companies. This paper aims to find the legal basis for the responsibility of technology companies for the realization of the protection of private life so that the main problem in this paper is the extent of the responsibility of technology companies for content containing elements of pornography.